Behavioral Patterns and Honey Yield Between Native and Non-native Stingless Bees in Bali's Ecosystem - Wahyudi, I Wayan; Suardana, Anak Agung Komang (Jurnal Biologi Tropis, 2025)
The coronavirus disease 2019 (COVID-19) pandemic has led to significant growth in honey bee cultivation in Bali, leading to the introduction of nonnative bee species alongside the indigenous Tetragonula laeviceps. However, the 75% failure rate of nonnative species cultivation between 2020 and 2023 necessitated a deeper understanding of species adaptability in the Bali ecosystem. This study specifically examined the behavioral adaptation and honey production of Heterotrigona itama compared with those of Tetragonula laeviceps in a shared cultivation environment. A seven-month comparative experimental study involving 30 bee colonies (15 H. itama introduced from Lampung and 15 local T. laeviceps) was conducted. Time series sampling was employed at three daily intervals (09:00, 13:00, and 16:00) for behavioral observations, while honey production was measured via nondestructive vacuum extraction. H. itama demonstrated superior honey production (516.3 ml average) to that of T. laeviceps (213.3 ml average). The species exhibited distinct foraging preferences, with T. laeviceps favoring Jatropha integerrima and H. itama preferring Antigonon leptopus and Xanthostemon chrynsanthus. Both species have developed different adaptive strategies for nectar–water content management, with H. itama utilizing sun exposure and T. laeviceps employing smaller storage pots. This study revealed successful coexistence between native and nonnative species through differentiated foraging behaviors and resource utilization strategies, with H. itama showing greater productive capacity attributed to morphological and behavioral differences.